Hydrogeological Modelling of Water-Level Changes in an Area of Archaeological Significance: A Case Study from Flag Fen, Cambridgeshire, UK. (2nd July 2016) - Wagstaff, Susan; Cheetham, James; Davis, Alice; Williams, Jim; Outram, Zoe; Priddy, Debbie; Chapman, Henry
Abstract : Concern exists regarding the long-term viability of the internationally important archaeological remains of the Flag Fen site near Peterborough. This paper describes a hydrogeological numerical groundwater model which has been used to understand the groundwater situation with regard to the archaeology, including drainage impacts, and also to explore future scenarios. Observed and modelled groundwater levels have been interpreted using three zones: the 'dry' zone 1 above the seasonal maximum water table; zone 2 of seasonal water table fluctuation; and a deeper zone 3 of permanent saturation. Archaeological wood is best preserved in Zone 3. Much of the Bronze Age wooden structure is located within Zone 2 or above. The hydrological conditions are therefore not ideal for the long-term in situ preservation of the material. Groundwater modelling indicates that the main factor controlling groundwater levels in the area is artificial drainage. The approach would be applicable to other wet-preserved archaeological sites.